2014
DOI: 10.1075/sic.11.3.05rog
|View full text |Cite
|
Sign up to set email alerts
|

The gradience of spirantization

Abstract: Most studies to date on the ability of English speakers to produce the Spanish approximants [β̞ ,ð̞ ,ɣ̞ ] have impressionistically looked at the stop-spirant contrast of English-speaking learners of Spanish (e.g. Zampini 1994, Díaz-Campos 2004, Face & Menke 2009), but no known study has empirically studied the degree to which these learners are able to spirantize when compared to native speakers. The current study looks at two groups of learners: one group composed of learners who had studied four semesters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…Because L2 speakers face little communicative pressure to acquire this type of target sound, acquisition may depend on a broader array of factors, including individual differences in motivation, willingness to communicate, and other personal characteristics. In that regard, Alvord and Christiansen (2012) and Rogers and Alvord (2014) reported that factors such as motivation and language use predicted advanced Spanish learners' spirantization of /b, d, g/.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because L2 speakers face little communicative pressure to acquire this type of target sound, acquisition may depend on a broader array of factors, including individual differences in motivation, willingness to communicate, and other personal characteristics. In that regard, Alvord and Christiansen (2012) and Rogers and Alvord (2014) reported that factors such as motivation and language use predicted advanced Spanish learners' spirantization of /b, d, g/.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have also addressed task type, demonstrating that learners produce more approximants on informal, semi-spontaneous speaking tasks such as an oral interview than on scripted tasks (Díaz-Campos 2006;Rogers & Alvord, 2014;Zampini, 1994). However, research in the area has typically crossed two features: whether tasks focus on form or meaning and whether they include orthography.…”
Section: Second Language Acquisition Of Spanish Approximantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous L2 intervocalic /d/ studies (Alvord & Christiansen, 2012; Face & Menke, 2009; González-Bueno, 1995; Rogers & Alvord, 2014; Solon et al, 2018; Zampini, 1994), it was hypothesized that L2-advanced speakers would begin with more approximant-like [ð] and also show more gains over time than L2-intermediate speakers. Based on Amengual (2019), it was hypothesized that Heritage-advanced speakers would produce more approximant-like [ð] at Time 1 compared to L2-advanced speakers, but as there are no previous studies of heritage Spanish speakers for intervocalic /d/ in the SA context, there was no formal hypothesis for Heritage-advanced speakers over time.…”
Section: Introductionmentioning
confidence: 99%